Need to belong and smartphone addiction risk: mediating role of anxiety symptoms and cognitive flexibility - Yılmaz, Selin (Journal of Dependence, 2025)
Objective: The main aim of the current study was to scrutinize the role of anxiety symptoms and cognitive flexibility in the relationship between the need to belong and smartphone addiction risk with the help of a model. Method: A total of 324 healthy university students, 214 female and 110 male, engaged in the study (M±SD age = 22.16 ±1.73). Need to belong, anxiety symptoms, cognitive flexibility, and smartphone addiction risk were measured via the Need to Belong Scale, Beck Anxiety Inventory, Cognitive Flexibility Scale, and Smartphone Addiction Scale, respectively. Results: Results of the Pearson correlation analyses indicated that the need to belong was positively correlated with anxiety symptoms (r = .28, p<.001) and smartphone addiction risk (r =.30, p<.001) and negatively correlated with cognitive flexibility (r = -.34, p<.001). In multiple mediation analysis, it was seen that there was a significant indirect effect of the need to belong on smartphone addiction risk through cognitive flexibility (b =.1417, SE =.06, 95%CI [0.03,0.27]) and anxiety symptoms (b = .2416, SE =.06, 95%CI [0.12, 0.37]). Conclusion: The need to belong may give rise to a smartphone addiction risk by increasing anxiety symptoms and decreasing cognitive flexibility.